Assessment of Disability Adjusted Life Years (DALYs) Among the Patients of Chronic Kidney Disease in Nishtar Medical University Hospital, Multan - Tufail , Nadia; HASAN, MUHAMMAD; USMAN, MOHAMMAD; AGHA, MUHAMMAD ASIM; SAEED, SANIA; SHABBIR, AHMAD; BASHIR, QASIM (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Mortality alone does not provide a clear picture of the illness burden experienced by individuals in various communities. The prevalence of CKD is increasing with an estimated global prevalence of 13.4%. However, in Pakistan, the prevalence was found to be 16.6%. DALYs are very useful in deciding how health resources should be distributed. Objectives: To highlight the importance of effective management strategies for patients with CKD in Pakistan and thus provoke the government and private sector to take specific measures thus reducing disability associated with CKD and increasing life expectancy. Material and Methodology: A cross-sectional comparative study was conducted in Nephrology Department of Nishtar Medical University Hospital, Multan. Questionnaire data on demographics, morbidity, and disability were analyzed using SPSS v22. Results: Out of 110 Chronic kidney disease patients, 62 were male (56.4%) and 48 were female (43.6%). The majority of patients were married. Most females were housewives and most men were unemployed. The sample size consisted mostly of participants which had an educational background ranging from illiterate to matriculation (75.4%). Only 24.5% had intermediate or higher education. Most patients spent 10–40k/month; fewer spent over 60k, then 40–60k. Most lacked CKD family history and were non‑smokers. 71.8% had ankle/feet swelling; 62.7% experienced skin itching, tingling, numbness. Conclusion: All CKD patients had ≥1 disability. Fatigue/exhaustion was the most common physical issue; depression, mood fluctuations, and mental confusion were the main functional disabilities. Most were low socioeconomic/educational and diagnosed late.